PENGARUH NILAI TUKAR TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR FOOD AND BEVERAGE DI MASA PANDEMI COVID-19 - Kartikaningsih, Dewi (BISMA: Jurnal Bisnis dan Manajemen, 2020)
The purpose of this study is to examine the effect of exchange rates on stock prices during the Covid-19 pandemic era. The population in this study was food and beverage companies listed on the Indonesia Stock Exchange. The research period was four months, from January 2, 2020, to May 8, 2020. Research data were collected based on the weak condition of the world economy and the Indonesian economy as the impact of Covid-19 and based on the phenomenon that the food and beverage business will reap profits amid the pandemic. This study used linear regression analysis with e-Views software. The results showed that the exchange rate affects the stock price of companies engaged in the food and beverage sector listed on the Indonesia Stock Exchange. Keywords: exchange rate, food and beverage, stock price